Unconventional teaching resources and their role in the organization of geography teaching at schools - Alencar, Josivane José de; Silva, Josélia Saraiva e (Geosaberes; Vol 9 No 18 (2018): May - Aug.DO - 10.26895/geosaberes.v9i18.645, 2018)
The teaching of geography taught at schools over the times with the use of encyclopedism, has had a change of re-signification of contents and themes, daily approached. This re-signification involves the development of different types of contents (conceptual, procedural and attitudinal), as well as the use of didactic resources. This article presents results of a bibliographical survey about the theme: "Didactic Resources and Teaching of School Geography" and it aims to broaden the knowledge of teachers about the potential of non - conventional didactic resources which make Geography leaning more meaningful for students of basic education.